2023
DOI: 10.3390/ani13111860
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Automatic Monitoring of Respiratory Health Conditions in Smart Swine Farming

Abstract: Porcine respiratory disease complex is an economically important disease in the swine industry. Early detection of the disease is crucial for immediate response to the disease at the farm level to prevent and minimize the potential damage that it may cause. In this paper, recent studies on the application of artificial intelligence (AI) in the early detection and monitoring of respiratory disease in swine have been reviewed. Most of the studies used coughing sounds as a feature of respiratory disease. The perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The number of coughing sounds or the severity of the respiratory disease might not be enough for the alarm to turn on. There is also a possibility that the differences of ReHS between groups might be due to population size difference since the technology was designed for large pig populations [26]. The result found that the ReHS and the CF have a strong negative association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of coughing sounds or the severity of the respiratory disease might not be enough for the alarm to turn on. There is also a possibility that the differences of ReHS between groups might be due to population size difference since the technology was designed for large pig populations [26]. The result found that the ReHS and the CF have a strong negative association.…”
Section: Discussionmentioning
confidence: 99%
“…AI product that can automatically detect and monitor the respiratory health status of pigs using sound technology is available in the market, the SoundTalks (SoundTalks NV, Leuven, Belgium) [26]. Several studies evaluate its applications in swine farming and show advantages over conventional method of health monitoring [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the further development of deep learning, intelligent cameras and recording devices have begun to be used in pig farms. They play an important role in disease monitoring [51], behavior monitoring [52], and video-based weight estimation [53]. The collection and storage of unstructured data such as video and audio also face challenges.…”
Section: Iot Of Pig Farmmentioning
confidence: 99%